2009
DOI: 10.1203/pdr.0b013e3181b9b4d3
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Intronic Mutation in the SLC12A3 Gene Leads to Gitelman Syndrome

Abstract: Many mutations have been detected in the SLC12A3 gene of Gitelman syndrome (GS, OMIM 263800) patients. In previous studies, only one mutant allele was detected in ϳ20 to 41% of patients with GS; however, the exact reason for the nonidentification has not been established. In this study, we used RT-PCR using mRNA to investigate for the first time transcript abnormalities caused by deep intronic mutation. Direct sequencing analysis of leukocyte DNA identified one base insertion in exon 6 (c.818_819insG), but no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Halpotype analysis with markers flanking the SLC12A3 demonstrated that c.1670 -191C3 T and c.2548ϩ253C3 T mutations are located on mutational hot spots rather than founder effect. Of interest, this c.1670 -191C3 T was only identified in Taiwan aborigines and identical to one reported from Japan and inherited from a Filipino maternal allele (35). Taiwan has been suggested to be the homeland of the Austronesian language family (36,37).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Halpotype analysis with markers flanking the SLC12A3 demonstrated that c.1670 -191C3 T and c.2548ϩ253C3 T mutations are located on mutational hot spots rather than founder effect. Of interest, this c.1670 -191C3 T was only identified in Taiwan aborigines and identical to one reported from Japan and inherited from a Filipino maternal allele (35). Taiwan has been suggested to be the homeland of the Austronesian language family (36,37).…”
Section: Discussionsupporting
confidence: 75%
“…A recent study reported that GS patients with truncated mutations or splicing variants in at least one allele tended to manifest more severe symptoms (16). We found that the reported female patient from Japan and our female patients carrying deep intronic mutation appeared to exhibit moderate to severe symptoms (35). Whether the phenotypes in GS are modified by the deep intronic mutations merits further investigation.…”
Section: Discussionmentioning
confidence: 47%
“…However, these studies did not fully consider the effect of splice site mutations on COL4A5 expression. This study requires careful analysis of COL4A5 transcripts and assessment of intronic mutations, which have been increasingly identified as a cause of aberrant splicing for various disorders, including Alport syndrome (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Recessive mutations were published in the SLC12A3 gene which encodes the Na-Cl cotransporter NCC(82). In up to 40% of patients the second mutation cannot be detected possibly due to deep intronic location or large genomic rearrangements(8385). A Ncc knockout mouse model confirmed the human GS phenotype with hypomagnesemia and hypocalciuria but lacked volume contraction and metabolic alkalosis(86, 87).…”
Section: Gitelman-like Hypomagnesemiasmentioning
confidence: 99%